Structural, morphological, magnetic and optical properties of Jeanbandyite prepared by the co-precipitation method. (March 2023) - El Hachmi, Abdelhadi; Sen, Subhadeep; Mondal, Rajib; Paul, Mohuya; Saha, Abhijit; Im, Jungkyun; Biswas, Goutam
Abstract: Jeanbandyite is one of the rare and unique structured minerals in the perovskite family. Jeanbandyite is a hydroxide perovskite having a formula of (Fe 3+ 1−x, ⎕x ) (Sn 4+ 1−y, ⎕y ) (OH)6 (⎕ = vacancy). Herein we report for first time the synthesis of jeanbandyite with superparamagnetic properties. The novel FeSnO(OH)5 compound is synthesized by a coprecipitation method, and the product has been analyzed using different characterization techniques, e.g., X-ray Diffraction (XRD), Mössbauer spectroscopy, Raman spectroscopy, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Scanning Transmission Electron Microscopy (STEM), Energy-Dispersive X-ray spectroscopy (EDS), Fourier Transform Infrared spectroscopy (FT-IR), and Vibrating Sample Magnetometer (VSM). The optical property (band gap) was measured using the UV-Vis spectroscopy. The characterization technique confirms the synthesis of the jeanbandyite, and the VSM study further reveals the superparamagnetic property. The band gap was found to be 2.85 eV, which indicates that this compound can be an effective photocatalyst in the near future. Graphical Abstract: ga1